The Utilization of the Project Portfolio Selection Methods in Prioritization of the Public Procurement Assignments : Case Study - Virtanen, Suvi (My University, 2023)
This Master’s thesis focuses on the prioritization of the public procurement assignments in the case organization. The case organization is a municipality, the City of Jyväskylä. The study problem in question occurs in the procurement service unit of the case organization when the work order for the procurement assignments is planned. The procurement assignments are assigned to the procurement service unit by other units in the case organization. This study aims to answer to the research question: How to prioritize the public procurement assignments? To answer the research question and define the research area explicitly, the following research objectives have been set: 1. To identify the relevant factors influencing on the prioritizing 2. To identify the existing project portfolio selection methods 3. To evaluate the suitability of those in the public procurement context. The literature review introduces municipality as an operative environment, the public procurement in the municipality, and the project portfolio selection process. This Master’s thesis was conducted as a desk study. The data for the analysis was collected from the documents of the case organization, from the reports concerning the previous research of the project portfolio selection methods and from the applications of the methods. The analysis was made in two parts. In the first part of the analysis, the relevant factors influencing the prioritization of the procurement assignments were identified in the case organization. The factors were categorized. Some were relevant for the prioritization process, other for the timeline of the process or the prioritization criteria. In addition, the requirements for the prioritization methods were identified. In the second part of the analysis, the selected project portfolio selection methods were assessed against the requirements identified in the first part of the analysis. The delimitation of the number of the project portfolio selection methods was based on the framework introduced in the study’s literature review. In the analysis the main decisive differences on these methods were identified to be the scalability of the method and the format of the results. Based on the assessment, three most suitable solutions for procurement assignment prioritization were the Q-Sort, the Analytical Hierarchy Procedure and the Weighted Scoring Model. The findings of this study are beneficial in the actual development of the public procurement prioritization process in the case organization. The practical recommendations for the process development and the definition of the criteria were given.
Keywords: public procurement; projects; portfolios; municipalities; public administration; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development